(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The objective of this work is to analyze the temporal and spatial variability of the total ozone column (TOC). The spatial, long-term, seasonal, and short-term variations of TOC in this region were analyzed. For the spatial variability, the latitudinal variability has a large range between 3 and 13, and also represents an annual cycle with maximum in February and minimum in August. In contrast, the longitudinal variability is not significant and just varies between 2 and 4. The long haul inconstancy likewise speaks to a striking increment in TOC for the period from 2004 to 2015 delineating the huge recuperation environmental ozone over Kathmandu. The ozone recuperation during the ongoing years might be because of the decrease of the ozone depletory operators. The Monitoring of worldwide ozone in the stratosphere is a fundamental precondition to understanding climatic science and the recuperation of stratospheric ozone all through the 21st century. This examination is critical as changes in environmental ozone will have significant outcome on people, plants and creatures.